(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to find out community participation in the development of the Birtaria Kassi tourist attraction in Jeneponto Regency. The method used a qualitative method which explained how the community participates in the development of the Kassi Birtaria tourist attraction in Jeneponto Regency. The research informants were 6 people. Research information was collected through observation, interviews and documentation. The results showed that community participation in the development of the Birtaria Kassi tourist attraction in Jeneponto Regency, seen from the planning had run well, namely the presence and activeness of the community in providing input during the meeting. Furthermore, the management was good where the community participates in the construction of facilities and infrastructure and participates in providing services for tourists. Furthermore, in the utilization stage, the community’s economy was increasing.